Credit Risk Management and Efficiency: Evidence from Islamic Banking System in Bangladesh - Akhter, Mst. Momena; Masum, Abdullah Al (Asian Accounting and Auditing Advancement, 2021)
The banking industry plays a vital role in the economic system by providing credit facilities to other industries. Banks act as intermediaries of funds in the financial market, and the most vital activities of banks is the assembly and distribution of financial resources to diverse segments of the economy. Administration in this industry has been planned to intensify the efficiency of lending, the credit assessment, and the capacity to pay back the principal and the interest for each customer’s credit limit. The recent paper attempts to examine whether credit risk management improves the efficiency of the Islamic commercial banks of Bangladesh. The study has been conducted under four stages of analysis. In the first stage, the nonparametric technique, Data Envelopment Analysis (DEA), was used to measure the efficiency of the Islamic Banks. In contrast, the second stage analyzed the credit risks using financial ratios. The third stage examined the association between credit risk and technical efficiency of the banks from 2015 to 2021 using Pearson Correlation analysis. Finally, the impact of credit risk management on the technical efficiency of the banks was tested by panel data analysis. Finally, the study found Exim Bank Limited to be the most technically efficient bank based on the variables to which they were put to the test. The study’s findings also revealed a significant positive relationship between credit risk management and the efficiency of the Islamic banks operating in Bangladesh.